Karma In The Hinduism And Buddhism Perspective - Husnul Khotimah; Muhammad Sandi Rosyadi (Jurnal Ilmiah Ilmu Ushuluddin, 2023)
This paper will explain about ideology that often called "Karma". The use of the word "Karma" generally intended to illustrate things that are not good; karma is always associated with bad karma. In fact, karma is not only bad but also good karma. Aside from being a bad karma, karma concept also often identified as the sole cause of the incident. The word "Karma" is popular in the teachings of Hinduism and Buddhism. However, there is still a lot of misunderstanding about the word "Karma" itself defined by people. As with Karma in Buddhism is a doctrine of punishment will be in getting from bad deeds, some are linking the poor health of a human being as Karma, and many misconceptions about karma. Understanding Karma seen in the perspective of Hinduism and Buddhism, while also finding out whether or not the similarity of understanding, teaching, the implementation of the Karma in Hinduism and Buddhism.